The relationship between depression, daytime napping, daytime dysfunction, and snoring in 0.5 million Chinese populations: exploring the effects of socio-economic status and age - Yuning Liu; Tingting Peng; Siqiao Zhang; Kun Tang (BMC, 2018)
Abstract Background Daytime napping has been postulated as both a protective and a risk factor for depression in previous studies. In addition to these conflicting results, research gaps also exist with regard to controlling confounding bias between daytime napping and depression and examining the potential association within the Chinese population. To facilitate the prevention and diagnosis of depression, this study aims to provide insight into the association of daytime napping and depression in 0.5 million Chinese adults by fully controlling confounders, and further examine the modifying effects of socio-economic status (SES) and age. Methods Data were drawn from the baseline of a Chinese cohort study of 0.5 million adults. Depressive status was measured by the Composite International Diagnostic Inventory (CIDI). Logistic regression models were used to examine the association between depression and daytime napping adjusted for SES, sleep-related factors, lifestyle factors and related diseases. Further stratified analyses were conducted to identify the modifying effects of socio-economic status and age. Results The odds ratio of depression by daytime napping was 1.15 (95% CI: 1.01-1.31) in females and 1.42 (95% CI: 1.18-1.71) in males. Factors including living in a rural area (OR = 1.31, 95% CI: 1.13-1.52), receiving less education (OR = 1.42, 95% CI: 1.22-1.66), getting married (OR = 1.24, 95% CI: 1.10-1.40) and being 45-65 years old (OR = 1.29, 95% CI: 1.12-1.49) had a modifying effect on daytime napping and depression that could strengthen the association. Conclusions A significantly positive association was found between depression and daytime napping, as well as daytime dysfunction, snoring and both shorter and longer sleep duration. Lower SES and age could possibly modify the association. Further clinical or epidemiological studies are needed to investigate the mechanism and facilitate the prevention of depression.